Depression and anxiety at time of implantable cardioverter defibrillator implantation and the biological link with cardiovascular disease. (24th May 2021) - Van Der Lingen, ACJ; Rijnierse, MT; Hooghiemstra, AM; Elshout, S; Van Halm, VP; Batelaan, NM; Van Rossum, AC; Pedersen, SS; Leeuwis, AE; Allaart, CP
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Psychological distress, such as symptoms of anxiety and depression, are frequently present in patients receiving an implantable cardioverter defibrillator (ICD) and they are associated with adverse outcomes. Multiple pathophysiological mechanisms may explain the link between psychological distress and cardiovascular disease, such as autonomic dysfunction, neuro-endocrine alterations and chronic inflammation. Purpose: The present study aims to examine the prevalence of psychological distress at time of ICD implantation and evaluates the complex interplay between psychological distress, autonomic function, neuro-endocrine alterations and inflammatory status in ICD patients. Methods: We conducted a prospective study that included ICD patients receiving an ICD for primary and secondary prevention of sudden cardiac death. Prior to implantation, patients underwent extensive psychological evaluation, including validated questionnaires for depression, anxiety and personality traits. Cardiac status was evaluated by left ventricular ejection fraction (LVEF) assessment, New York Heart Association (NYHA) functional class evaluation, 6-minute walk test (6MWT), and 24-hour Holter monitoring for heart rate variability (HRV). Thyroid function, catecholamine levels and inflammatory status were also evaluated. Results: Of 178 patients included (age 64 ± 12, 79% male, LVEF 35 ± 13%), 35% had symptoms of depression and 32% had symptoms of anxiety. Symptoms of depression and anxiety increased significantly with higher NYHA functional class (P < 0.001). Depressive symptoms were associated with a reduced 6MWT (411 ± 128 m versus 488 ± 89 m, P < 0.001), lower LVEF (29 ± 9% versus 36 ± 13%, P = 0.03), higher heart rate (74 ± 13 bpm versus 70 ± 13 bpm, P = 0.02), higher thyroid stimulating hormone levels (1.8 [1.3-2.8] mU/L versus 1.5 [1.0-2.2] mU/L, P = 0.04) and multiple HRV parameters, indicating reduced HRV. Anxiety symptoms were only associated with a reduced 6MWT (433 ± 112 m versus 477 ± 102, P = 0.02). Symptoms of depression or anxiety were not correlated with c-reactive protein, NT-proBNP or catecholamine levels. Conclusion: A substantial part of ICD patients has symptoms of depression and anxiety at time of ICD implantation. Depression was correlated with a higher NYHA class, reduced exercise capacity,   reduced LV-function and alterations in autonomic function, suggesting a biological link between depression and cardiac status. Whether depression and anxiety leads to an increase in ventricular arrhythmias will be determined during further follow-up.